1991
DOI: 10.1128/iai.59.11.4221-4226.1991
|View full text |Cite
|
Sign up to set email alerts
|

Release of leukotriene B4 from human neutrophils after interaction with nontypeable Haemophilus influenzae

Abstract: Opsonization of nontypeable Haemophilus influenzae with antibody is critical for the interaction between the organism and human polymorphonuclear leukocytes (PMNs). Nontypeable H. influenzae opsonized in fresh antibody-positive serum induced the release of 42.5 ± 17.9 ng of leukotriene B4 per ml from PMNs after 20 min of incubation at 37°C. On the other hand, opsonization of the organisms in fresh antibody-negative serum stimulated the release of significantly smaller amounts of leukotriene B4 by the PMNs. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Bacterial aggregation or bactericidal activity of the serum could have reduced the number of viable bacteria. Garofalo et al (11), measuring the association of radioactive labeled bacteria with PMNs at a bacterium/PMN ratio of 10:1, did not include controls to assess the viability of the bacteria, which we found to be an important factor. Heat-killed bacteria were opsonophagocytized better than viable bacteria (Fig.…”
Section: T Viable Killedmentioning
confidence: 85%
“…Bacterial aggregation or bactericidal activity of the serum could have reduced the number of viable bacteria. Garofalo et al (11), measuring the association of radioactive labeled bacteria with PMNs at a bacterium/PMN ratio of 10:1, did not include controls to assess the viability of the bacteria, which we found to be an important factor. Heat-killed bacteria were opsonophagocytized better than viable bacteria (Fig.…”
Section: T Viable Killedmentioning
confidence: 85%
“…Studies of the generation of eicosanoids in human blood after the phagocytosis of zymosan showed that LTB4 synthesis increased to maximum levels from 30 to 60 min after the stimulus and remained essentially constant thereafter for at least another hour (12). Also, increased LTB4 release by PMN parallels the kinetics of opsonic phagocytosis of H. influenzae in vitro (14). Finally, in an animal model of colonic inflammation, increased LTB4 synthesis correlated with PMN infiltration for a duration of several weeks (50).…”
Section: Discussionmentioning
confidence: 97%
“…The necessity for complement in the phagocytic process is somewhat controversial. In our experience, phagocytosis can occur in the presence of antibody alone; however, complement augments the process 47 . In contrast, studies conducted by Troestra et al 46 and Musher et al 48 attribute greater importance to the role of complement.…”
Section: Igg‐specific Antibody Response (μG/ml) Of Children With Acutmentioning
confidence: 56%
“…In contrast, studies conducted by Troestra et al 46 and Musher et al 48 attribute greater importance to the role of complement. From our own studies, it is clear that phagocytosis is associated with the release of leukotriene B4, a potent chemoattractant for neutrophils 47 . Thus, the inflammatory response is heightened.…”
Section: Igg‐specific Antibody Response (μG/ml) Of Children With Acutmentioning
confidence: 94%